Trastuzumab deruxtecan for the treatment of HER2-positive gastric cancer. (3rd July 2021) - Mishima, Saori; Shitara, Kohei
ABSTRACT: Introduction : Trastuzumab deruxtecan (T-DXd) is a novel human epidermal growth factor receptor 2 (HER2)-targeted antibody–drug conjugate with a humanized anti-HER2 antibody, cleavable peptide-based linker, and topoisomerase I inhibitor payload. The phase II trial DESTINY-Gastric01 has demonstrated that T-DXd exhibits antitumor activity in patients with HER2-positive advanced gastric cancer (AGC) who had received at least two previous therapies, including trastuzumab. Area covered : T-DXd was approved for previously treated HER2-positive AGC in Japan. The US Food and Drug Administration also approved on 15 January 2021. In this article, we review the development of T-DXd, its pharmacology, and its safety profile in patients with HER2-positive AGC. Expert opinion : T-DXd has demonstrated a significantly higher objective response rate and a longer overall survival in HER2-positive AGC patients with two or more previous lines of systemic chemotherapy, including trastuzumab. Safety profile was acceptable. Currently, there are several ongoing clinical trials of T-DXd in combination with cytotoxic chemotherapy or an immune checkpoint inhibitor.